2020
DOI: 10.1111/jce.14371
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of His‐bundle pacing in patients with conduction disorders following transcatheter aortic valve replacement

Abstract: Background Conduction disorders requiring permanent pacemaker implantation occur frequently after transcatheter aortic valve replacement (TAVR). This multicenter study explored the feasibility and safety of His bundle pacing (HBP) in TAVR patients with a pacemaker indication to correct a TAVR‐induced left bundle branch block (LBBB). Methods Patients qualifying for a permanent pacemaker implant after TAVR were planned for HBP implant. HBP was performed using the Select Secure (3830; Medtronic) pacing lead, deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…His bundle pacing (HBP) has been a recommended pacing modality for the above‐mentioned patients who have CAs after PVs implantation 19,20 . Given that few nonspecific intraventricular conduction disease or peripheral conduction block may occur in this specific patient population, HBP may have a unique role, as it realizes electrical synchrony via His‐Purkinje system recruitment and QRS correction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…His bundle pacing (HBP) has been a recommended pacing modality for the above‐mentioned patients who have CAs after PVs implantation 19,20 . Given that few nonspecific intraventricular conduction disease or peripheral conduction block may occur in this specific patient population, HBP may have a unique role, as it realizes electrical synchrony via His‐Purkinje system recruitment and QRS correction.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proved that TAVR valve type and depth of implantation are the most important procedural associations with conduction damage 22 . Pooter et al reported a success rate of 69% in LBBB correction with acceptable pacing thresholds under HBP 20 . Their results suggested that a more significant involvement of CAs at the level of a more distal site in the conduction system may lead to a lower success rate in HBP 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Sen et al 8 reported a case of HBP in a patient with TAVR‐induced NO‐LBBB, without correction of LBBB. De Pooter et al 9 reported that HBP with LBBB correction with an acceptable pacing threshold was achieved in 11 of 16 (69%) in patients developing LBBB after TAVR. Chen et al 10 reported the anatomical evaluation of LBBP in an in vivo canine model which said that the HBP lead was located at the right septum on the ventricular aspect of the tricuspid valve, and the LBBP lead was placed deeply with the ring of the lead inside the septum.…”
Section: Discussionmentioning
confidence: 99%
“…The damage resulting from mechanical displacement during aortic valve deployment might be permanent. Pacing at the His bundle may correct LBBB 8–9 . However, the correction of LBBB by HBP usually requires a higher pacing electrical output, negatively impacting on the therapy effectiveness and device longevity.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of the Journal of Cardiovascular Electrophysiology , De Pooter et al 6 report their multicenter experience on His‐bundle pacing (HBP) in 16 patients developing LBBB after TAVR (the Evolut TM R valve; Medtronic, Minneapolis, MN). Successful HBP with LBBB correction with an acceptable pacing threshold was achieved in 11 of 16 (69%).…”
mentioning
confidence: 99%